Meningkatkan Berpikir Kreatif Dan Kerjasama Siswa Menggunakan Model Bhinneka Di Kelas V SDN Murung Raya 4 Banjarmasin - Lisa Muzdhalifah Hayati; Noorhapizah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research investigates the low levels of creative thinking skills and teamwork abilities among fifth-grade students at SDN Murung Raya 4 Banjarmasin. The contributing factors include a lack of student responsibility towards learning, laziness, insufficient student engagement, and a limited variety of teaching models and media. To address this issue, the research implements the BHINNEKA teaching model. The objective of this research is to evaluate student activities, creative thinking skills, and teamwork abilities. The methodology employed is Classroom Action Research (CAR), with the research subjects being the fifth- grade students at SDN Murung Raya 4 Banjarmasin. The approach used encompasses both qualitative and quantitative methods. The research findings indicate that the assessment of the teacher's activities during meetings 1 to 4 achieved a very good level. Creative thinking skills, which initially scored "Very Few Students Skilled" in meeting 1, improved to "Almost All Students Highly Skilled" in meeting 4. Similarly, teamwork abilities, initially categorized as "Very Few Students Capable" in meeting 1, advanced to "Almost All Students Highly Capable" in meeting 4. Based on these findings, it is concluded that the BHINNEKA model is effective in enhancing creative thinking skills and teamwork abilities. It is recommended that this model be used as an alternative to improve the quality of education.